Legal Deposit in Denmark - the New Law and Electronic Products - Dupont, Henrik (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
In 1997 Denmark celebrated the tricententenary of its legal deposit legislation and at the same time created a new law that surpassed the former 1927 text, which was out of date due to technological and political developments. In the first law on legal deposit, maps were not mentioned explicitly and we have no known examples of maps delivered before a revision of the law in 1781, which explicitly stated that maps and prints had to be deposited. It was only after 1850 that it became possible to follow what was deposited exactly. The number of maps deposited before was limited, not even including the first national survey maps. Maps were only produced in a limited number and the annual deposit did not exceed 600. We assume that all in all some 40,000 maps have been delivered to the collections by legal deposit. Each year since the Second World War the maps have been listed in the annual „Dansk Kortfortegnelse” and since 1980 all new maps have been catalogued in the REX database of the Royal Library.